Aortic root dilatation among children with unoperated Fallot tetralogy. A clinical and echocardiographic study. - Alsuwayfee, Khaleel I. (Journal of the Faculty of Medicine Baghdad, 2016)
Bacground: Tetralogy of Fallot (TOF) is a commn congenıtal heart disease and it may be associated with aortic root dilation (ARD ) before or even years after the surgical repair. To the best knowledge this is the first study in Iraq dealing with this issue.Objectives : To dtermine the frequency of aortic root dilatation among sample of children with Fallot teralogy in Mosul-İraq and to asses its associated risk factors.Patients and methods : A total of 110 children ,54 with TOF compared to 56 normal chıldren by echocardiography for determining the frequency of aortic root dilatation among both groups. Among TOF children different factors like age and sex, size of the ventricular sptal defect (VSD) ,degree of overrıdıng of aorta over the interventricular septum, severity of the right ventricular outflow tract (RVOT) obstruction , positive family history of TOF affecting other family member , the presence of previous paliative surgery like Blalock-Taussig shunt and the use of Beta receptors blocking drugs were evaluated for its possible association with the problem.Results: Fifty four children with TOF (male :female=0.45) , mean age 67.55 ± 51.8 months and mean body surface area (BSA) 0.71± 0.47 m2 were compared to fifty six normal chıldren (male :female=0.46) , mean age 47.64 ± 39.59 months and mean BSA 0.60 ± 0.24 m2. The frequency of ARD among children with unoperated TOF was high (69 %) in the studied sample and goes with what was already known (15%-87%). Male sex , increasing patient age and severe (RVOT) obstruction with pulmonary hypoplasia were positivelly correlated with the increased risk of the development of ARD while the other factors did not show significant association.Conclusion: Aortic root dilatation should be considered seriously in children with TOF and when ever possible surgical correction should be performed after infancy.